The implication of occupational stress toward employee job performance at KPJ Rawang Specialist Hospital / Siti Nur Amalina Azman - Azman, Siti Nur Amalina (Faculty of Business and Management, 2018)
The purpose of this research study is to investigate the relationship between level of occupational stress toward employee job performance at KPJ Rawang Specialist Hospital. There are several factor will be discussed under this research study which consist of Workload, Poor Working Condition, Role Ambiguity and Inadequate Monetary Reward. There are few study had been conducted by previous researchers will be the references to hypothesis development in this research project. The sample size of 80 respondents had been conducted and simple random sampling method been used to distributed the questionnaires to the selected respondents. The sample size is selected from all support services at KPJ Rawang Specialist Hospital which consist of Administration, Talent Management, Information Technology, Finance, Credit control, Billing and Admission, Marketing and Public Relation, Purchasing and Maintenance Department. This research also aimed to identify the frequency and descriptive of data collected, the relationship between variables, reliability analysis and hypothesis testing among the variables using Statistical Package Social Science (SPSS) Software. The result between these factor has positive significant relationship with employee job performance at the organization. The final chapter of this research study will elaborately explain the conclusion of research finding and suggested recommendation to future research have been done.